Administration of teriparatide improves the symptoms of advanced bisphosphonate-related osteonecrosis of the jaw: preliminary findings. Issue 12 (December 2015) - Kakehashi, H.; Ando, T.; Minamizato, T.; Nakatani, Y.; Kawasaki, T.; Ikeda, H.; Kuroshima, S.; Kawakami, A.; Asahina, I.
Abstract: Teriparatide is a synthetic polypeptide hormone that contains the 1–34 amino acid fragment of the recombinant human parathyroid hormone that stimulates bone formation. Currently, it is approved only for the treatment of osteoporosis. The outcomes of daily teriparatide injections for the treatment of bisphosphonate-related osteonecrosis of the jaw in 10 patients are reported here. Two of the 10 cases dropped out due to adverse events. Of the remaining eight cases, seven exhibited clinical improvement of the jaw-related symptoms of osteonecrosis and progression of the sequestration, while one case did not show improvement of the symptoms. Administration of teriparatide in patients with osteonecrosis of the jaw promotes bone formation and subsequent sequestration over a short period of time. These results suggest that adjunctive teriparatide therapy is a viable and effective option for treating osteonecrosis of the jaw.